The Commodification of Water in the Arid and Semi-Arid Parts of South Africa: A Preliminary Historical Exploration (Historia, 2021)
EnglishThe commodification of water is a spin-off from the rapid advances made by liberal capitalism in all parts of the world since the late-twentieth century. Increasingly water, traditionally considered as being a natural resource, has become subject to commodification. In this article an overview is given of the human consumption of water in the arid and semi-arid parts of Southern Africa. Consideration is given to the San and Khoikhoi’s traditional patterns of using water. Working from the premise of transition from hunting, gathering and foraging to pastoralism, it is clear that even in the more arid regions, water was freely accessible in the pre-colonial history of South Africa. In the colonial period, as from 1652, tracts of land with water-supplies fitted into a new dispensation of land tenure. This had a negative impact on indigenous hunter-gatherers and pastoralists. It also affected patterns of waterconsumption as the population of pastoralists in the interior of the subcontinent increased. By the time the South African mining revolution started at the copper-mines of Okiep in the 1850s, water had become a commodity. Furthermore, the rapid introduction of technology to procure more water – boreholes and mills for subterranean water-supplies and irrigation schemes for agricultural development from surface supplies – augured in an era of commodification that continued unabatedly until the 1990s. When it was introduced into the political arena as a part of democracy and an extension of human rights, the importance of water became apparent. The government’s policy of free water, is seen as part of the decommodification of the resource, subject however, to certain provisos.    AfrikaansDie Kommodifisering van Water in die Dor en Semi-Droë Gebiede van Suider-Afrika: ’n Voorlopige Historiese Verkenning Die kommodifisering van water is die resultaat van die snelle vooruitgang wat liberale kapitalisme sedert die laat-twintigste eeu in alle wêrelddele gemaak het. Water, wat tradisioneel as ’n basiese hulpbron beskou is, het toenemend ’n kommoditeit geword. In hierdie artikel word ’n oorsig van waterverbruik (vir mens en dier) in die dor en semi-droë gebiede van Suider-Afrika gegee. Oorweging word geskenk aan die San en Khoikhoi se tradisionele patrone van watergebruik. Daar word gewerk vanuit die verwysingsraamwerk van die menslike oorskakeling van jagter-versamelaar- na veeherdergemeenskappe. Daaruit blyk dit dat water in die pre-koloniale geskiedenis van Suid-Afrika in die droë gebiede van Suid-Afrika gratis vir alle gebruikers beskikbaar was. Gedurende die koloniale tydperk, vanaf 1652, is grond toenemend onder stelsels van grondbesit gekonsolideer. Dit het ’n negatiewe impak op inheemse jagter-versamelaars en veeherders gehad. Dit het ook namate die veeboerbevolking toegeneem het, die verbruikspatrone van water geraak. Teen die tyd dat die Suid-Afrikaanse mynbou-omwenteling in die 1850’s met kopermynbou-aktiwiteite ’n aanvang geneem het, was water ’n kommoditeit. Daarby het snelle tegnologiese hulpmiddels om water te ontgin – boorgate en meulens vir ondergrondse voorrade en besproeiingskemas vir landbou uit bogrondse voorrade – ’n nuwe era van kommodifisering ingelui wat tot die 1990’s geduur het. Sedertdien het water ’n deel van die politieke debat in die land geword. Dit was spoedig deel van die gesprek oor demokrasie en ’n verlengstuk van menseregte. Die belangrikheid van dié hulpbron was dus vanselfsprekend. Die Regering se beleid van gratis water word teen hierdie agtergrond gesien as ’n poging om water te dekommodifiseer, maar met bepaalde voorbehoude.
Keywords: Water-history; water-use; commodification; irrigation; Southern Africa; semi-arid and arid regions; sustainable development; indigenous traditions; Watergeskiedenis; waterverbruik; kommodifisering; besproeiing; Suider-Afrika; semi-dor en droë streke; volhoubare ontwikkeling; inheemse tradisies